Object Vibration Tracking in Silent Video for Sound Extraction - เพียรตระกูล ธนัสนี; คุณวิภูษิต ภัทราวุธ; เจริญสาธิต กฤษฎิ์; เจริญสาธิต กฤษฎิ์ (RMUTL Engineering Journal, 2019)
This research proposed the steps of voice synthesis from videos, which contain a moving object. Video images with the suitable resolution are processed to locate the vibrating object. Then, the signals are magnified in order to easily detect the change in position. The moving positions of the object in each frame are converted to sound. The initial testing shows that the vibration of object in a video can be converted to sound with frequency close to the actual frequency of the source. This process of sound extraction can be used to assist in the investigation of a crime or incident.